Manto da apresentação: Arthur Bispo do Rosário em diálogo com Deus - Figueiredo, Alda de Moura Macedo (2010)
In Christmas Eve, 1938 Arthur Bispo do Rosário presented himself as Jesus Christ at São Bento s Monastery, in Rio de Janeiro, escorted by seven angels with the mission of judging alive and dead ones, in addition to catalogue the world in miniatures in order to give them to Father at the Day of Judgement. After this meeting with the monks the Son of Man was steered towards the Hospital Nacional dos Alienados; the quiet course of the ordinary, black, poor, north-eastern immigrant man's life had taken another direction to his mission's function on earth. The door to Arthur Bispo do Rosário's maze was open. The present dissertation investigates the uncommon life of the man who materialized into art the expectation of the meeting with God. A production surrounded by a mystic aura executed during half a century waiting for death. Arthur Bispo do Rosário's artistic motivation had been the wrong way down his time, because while he prepared himself to the solemn moment of his passage, science searched a way to declare the death's death. The artistic making of Bispo do Rosário was understood here as an experience lived in a broken time from the moment defined by the hierophants he lived, turning his 802 works into only one, while all of them were sewed by the same conductor thread of the production's aim. Among Arthur Bispo do Rosário's grand work one will deserve highlight the Manto da Apresentação (The Presentation Cape). According to its symbolic grandiosity within the labor of expectation's context, this work was identified as the mobile Center of the World. It's about a cloth embroidered inside and out during thirty years to be used at Father and Son grand meeting moment, moment in which the world would be given to the Almighty through its inventor's hands. In the Manto (Cape) its possible to perceive the sacred's manifestation that lead this labor of faith's artistic drudgery. The proposal is to turn attention to the artistic production of Bispo do Rosário to see his dialog with God